On the Study of Oscillons in Scalar Field Theories: A New Approach - Correa, R. A.C. [UNESP]; De Souza Dutra, A. [UNESP] (Hindawi, 2016)
We study configurations in one-dimensional scalar field theory, which are time-dependent, localized in space, and extremely long-lived, called oscillons. How the action of changing the minimum value of the field configuration representing the oscillon affects its behavior is investigated. We find that one of the consequences of this procedure is the appearance of a pair of oscillon-like structures presenting different amplitudes and frequencies of oscillation. We also compare our analytical results to numerical ones, showing excellent agreement.